Exploring nuclear structure with multiparticle azimuthal correlations at the LHC - Acharya, Shreyasi; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Grünwald, Nadine; Menzel, Marius; Nath, Abhishek; Pachmayer, Yvonne C.; et al. (Physics letters, 2025)
Details of the nuclear structure of 129Xe, such as the quadrupole deformation and the nuclear diffuseness, are studied by extensive measurements of anisotropic-flow-related observables in Xe-Xe collisions at a centre-of-mass energy per nucleon pair sNN=5.44 TeV with the ALICE detector at the LHC. The results are compared with those from Pb-Pb collisions at sNN=5.02 TeV for a baseline, given that the 208Pb nucleus exhibits a very weak deformation. Furthermore, comprehensive comparisons are performed with a state-of-the-art hybrid model using IP-Glasma+MUSIC+UrQMD. It is found that among various IP-Glasma+MUSIC+UrQMD calculations with different values of nuclear parameters, the one using a nuclear diffuseness parameter of a0=0.492 and a nuclear quadrupole deformation parameter of β2=0.207 provides a better description of the presented flow measurements. These studies represent the first systematic exploration of nuclear structure at TeV energies, utilizing a comprehensive set of anisotropic flow observables. The measurements serve as a critical experimental benchmark for rigorously testing the interplay between nuclear structure inputs and heavy-ion theoretical models.